Study on the Use of Banana and Pineapple Peel Waste as Biofertilizers: Enhancing soil fertility, Promoting Sustainable Agriculture and Environmental Sanitation - Mustapha, M.; Alasa, J. J.; Bashir, A. U.; Mohammed, B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Indiscriminate agricultural waste disposal especially fruits peels can cause environmental pollution with increased public health risk. This study deals with managing banana and pineapple peel waste as organic fertilizers towards promoting sustainable environmental sanitation and agriculture production. Waste of banana and pineapple peels were separately collected in households, dumpsites and markets, the collected fruits peels were cleaned, sun dried for 33 days and grounded into powdered form. Three different formulations of organic fertilizers were made from the sun dried and finely grounded fruit peels of banana and pineapple, namely; formulation A containing 100g of banana peels powder; formulation B containing 100g of pineapple peels powder and formulation C containing 100g of a mixture of banana and pineapple peels powder. Four different containers were used to collect 10kg of soil each, three of which were treated with the three formulations and named sample A, B, C and an additional sample D which is control. After 30 days of treating the soil with the different formulations. The result of laboratory soil analysis showed that; Sample A contains 14% Nitrogen, 37% Phosphorus, 7% Potassium, 40% Calcium and 2% Magnesium. Sample B contains 11% Nitrogen, 39% Phosphorus, 8% Potassium, 39% Calcium and % Magnesium. Sample C contains 17% Nitrogen, 35% Phosphorus, 4% Potassium, 43% Calcium and 1% Magnesium. Sample D (Controlled Soil Sample) contains 1% Nitrogen, 17% Phosphorus, 4% Potassium, 45% Calcium and 33% Magnesium. It was revealed that the fruit peel powder formulations can increase the soil fertility which serves as alternative replacement for chemical fertilizers towards sustainable agriculture and the environment. It is recommended that the farmers and general public should make beneficial use of fruits waste as organic fertilizers and not to be discarded indiscriminately.